Cost and Utility of Routine Contrast-Enhanced Neck MRA in a Pediatric MRI Stroke Evaluation Protocol - Baltensperger, A.; Mirsky, D.; Maloney, J.; Neuberger, I.; Fenton, L.; Bernard, T.; Borgstede, J.; Stence, N. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Cervical arterial dissection is one of the frequent causes of pediatric arterial ischemic stroke. Out of concern for missing cervical arterial dissection in patients in whom pediatric stroke is suspected, our tertiary children’s hospital added contrast-enhanced 3D neck MR angiography to every pediatric stoke work-up. This research investigated whether the routine use of contrast-enhanced neck MRA in our MR imaging stroke protocol ever detected a cervical arterial abnormality when the DWI, SWI/gradient recalled-echo, or circle of Willis MRA findings from the brain MR imaging were reported as normal.MATERIALS AND METHODS: The institutional PACS data base was searched for stroke protocol MRIs that included DWI, gradient recalled-echo or SWI, circle of Willis MRA, and 3D contrast-enhanced neck MRA in patients younger than 18 years of age with examinations performed between September 2010 and June 2017.RESULTS: In only a single case (0.15%) were the DWI, SWI/gradient recalled-echo, or circle of Willis MRA findings all separately reported as normal and the contrast-enhanced neck MRA findings reported as abnormal. To reach these findings, we screened 681 patients, which would have resulted in an estimated >$200,000 in Medicare charges and $80,000 in of out-of-pocket cost to patients.CONCLUSIONS: In our large series, the addition of a routine contrast-enhanced neck MRA to our pediatric stroke MR imaging protocol was of extremely low yield. We believe the use of neck MRA should reasonably be limited to cases in which abnormalities are initially detected on standard brain sequences or to patients with atypical presentation or recurrent pathology.AISarterial ischemic strokeCADcervical arterial dissectionCEcontrast-enhancedCoWcircle of WillisGREgradient recalled-echoVEN_BOLDvenous blood oxygen level–dependent